L-Proline, a resolution agent able to target both enantiomers of mandelic acid: an exciting case of stoichiometry controlled chiral resolution. Issue 61 (11th July 2022) - Zhou, Fuli; Collard, Laurent; Robeyns, Koen; Leyssens, Tom; Shemchuk, Oleksii
Abstract : l -Proline is used to resolve both enantiomers of mandelic acid through a stoichiometry controlled chiral resolution. Abstract : We present a thought-provoking development in chiral resolution. Using a resolving agent of a given handedness, l -proline, we show that both R- and S-enantiomers of mandelic acid can be resolved from a racemic mixture simply by varying the stoichiometry. We are the first to report this specific feature, achieved by the existence of stoichiometrically diverse cocrystal systems between R- and S-mandelic acid and l -proline.